Understanding the food and nutritional experiences of older adults living in rental flats: a contextualised socio-ecological study on food insecurity - Ong, Clarence (Nanyang Technological University, 2022)
Older adults are also particularly susceptible to food insecurity, thus eroding their self-perception of health and quality of life. In Singapore, there is a 30% rate of nutritional risk across the elderly population, which necessitates better understanding of the state of food insecurity and the potential drivers of this endemic. This study endeavours to understand the intersectionality of ageing and low socioeconomic status on food intake and food insecurity through an analysis of the lived experience of older adults living in rental flats (OALRF). By adapting the socioecological model in the context of the dimensions of food security, this paper seeks to establish a framework to decipher the interplay of factors that affect the food and nutrition experiences of OALRF, and the state of food security amongst this population. Qualitative interviews discovered factors such as health condition, limited budget, cohabitation, community agencies and food subsidies as being impactful in their decision-making process. While food was widely available, dimensions of accessibility, adequacy, acceptability and agency were still severely lacking for OALRF. Recommendations to improve on conditions include a community kitchen, a national food stamp programme, and a collaborative model between community partners and OALRF.